2012
DOI: 10.1063/1.3676044
|View full text |Cite
|
Sign up to set email alerts
|

Large anisotropic remnant magnetization tunability in (011)-La2/3Sr1/3MnO3/0.7Pb(Mg2/3Nb1/3)O3-0.3PbTiO3 multiferroic epitaxial heterostructures

Abstract: A large anisotropic remnant magnetization tunability was observed in multiferroic (011)-La2/3Sr1/3MnO3/0.7Pb(Mg2/3Nb1/3)O3-0.3PbTiO3 (LSMO/PMN-0.3PT) epitaxial heterostructures. The remnant magnetization along [100] direction was suppressed by an electric field applied to the substrate while the remnant magnetization along [011¯] was enhanced. The tunabilities of the remnant magnetization along the [100] and [011¯] directions are about −17.9% and +157% under electric field of +7.27 kV/cm, respectively. This la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 26 publications
1
38
1
Order By: Relevance
“…2, T C shifts from 117 K to 115 K with an electric field of 8 kV/cm. According to the earlier reports8910, the magnetization of the strain-mediated ME system is usually modified by altering the magnetic anisotropy, giving rise to an extrinsic CME effect. However, in the case of SRO/PMN-PT heterostructure, not only the magnetization but also T C varies with the electric field, suggesting that the CME effect in SRO film may have other coupling mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2, T C shifts from 117 K to 115 K with an electric field of 8 kV/cm. According to the earlier reports8910, the magnetization of the strain-mediated ME system is usually modified by altering the magnetic anisotropy, giving rise to an extrinsic CME effect. However, in the case of SRO/PMN-PT heterostructure, not only the magnetization but also T C varies with the electric field, suggesting that the CME effect in SRO film may have other coupling mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, the most used CME mode is the strain-mediated coupling17. By depositing the ferromagnetic component on ferroelectric/piezoelectric substrate, the electric-field-induced strain can remarkably manipulate magnetization, giving rise to large ME effects8910. Pb(Mg 1/3 Nb 2/3 )O 3 –PbTiO 3 (PMN-PT) and PbZr x Ti 1-x O 3 (PZT) are frequently selected as the ferroelectric/piezoelectric substrates due to their excellent piezoelectric and ferroelectric performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Many experiments demonstrated that the electric field can modulate the magnetic properties of the FM films including Curie temperature, saturation moment, remanence and coercivity by changing the magnetic anisotropy via the electric field induced strain in the FE substrates. [5][6][7] Recently, the heterostructures composed of epitaxial perovsike manganite films and FE substrates 6,8,9 was considered as a promising platform for studying strain-mediated ME coupling and attracted intense attention due to the abundant physical content in the manganite films such as Jahn-Teller distortion, double-exchange coupling, phase separation and so on. Due to the strong interplay among lattice, spin, charge and orbital degrees of freedom, the lattice strain can largely modulate various novel physical phenomena of the manganite film by modifying the MnO 6 distortion and thus the Jahn-Teller coupling.…”
mentioning
confidence: 99%